2005
DOI: 10.1111/j.1472-765x.2005.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of sorbitol-negative or slow-fermenting (suspected O157) Escherichia coli isolated from milk samples in Lombardy region

Abstract: Aims: To investigate phenotypic and genotypic aspects of sorbitol-negative or slow-fermenting Escherichia coli, suspected to belong to O157 serogroup, isolated in Italy. Methods and Results: Milk samples originating from goats and cows were screened for the presence of E. coli O157 with cultural methods. Sorbitol-negative or slow-fermenting strains were subjected to phenotypic characterization, antibiotic resistance profiles, PCR reactions for detection of toxins (stx 1 and stx 2 ) and intimin (eae GEN and eae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
1
6
0
4
Order By: Relevance
“…Perelle et al 16 examined samples of raw bovine milk in France and reported an overall STEC prevalence of 21% with only 4.8% of the samples containing serogroups of major public health concern including O26, O103, O111, O145 and O157. Oksuz et al 17 form Turkey, Picozzi et al 18 from Italy and Cizek et al 19 from the Czech Republic, reported that 1%, 0.7% and 2.0% raw cow samples were positive for E. coli O157, respectively. However, similar studies on raw cow's milk performed in the UK (Scotland) analyzing 500 samples 20 , in the Netherlands analyzing 1011 samples 21 , in Greece analyzing 100 samples 10 , and in Brazil analyzing 50 samples 22 resulted in no E. coli O157:H7 isolation.…”
Section: Discussionmentioning
confidence: 97%
“…Perelle et al 16 examined samples of raw bovine milk in France and reported an overall STEC prevalence of 21% with only 4.8% of the samples containing serogroups of major public health concern including O26, O103, O111, O145 and O157. Oksuz et al 17 form Turkey, Picozzi et al 18 from Italy and Cizek et al 19 from the Czech Republic, reported that 1%, 0.7% and 2.0% raw cow samples were positive for E. coli O157, respectively. However, similar studies on raw cow's milk performed in the UK (Scotland) analyzing 500 samples 20 , in the Netherlands analyzing 1011 samples 21 , in Greece analyzing 100 samples 10 , and in Brazil analyzing 50 samples 22 resulted in no E. coli O157:H7 isolation.…”
Section: Discussionmentioning
confidence: 97%
“…Milk and milk products have been involved in few cases (Ansay and Kaspar, 1997;CDSC, 1998). Since the presence of VTEC O157 has been reported in cow, goat, and ewe milk (Conedera et al, 2004;Picozzi et al, 2005) and given the particular resistance of O157:H7 and other EHEC strains to environmental conditions (especially to low pH values) (Meng et al, 2001), some milk products may increase the risk of pathogenic E. coli contamination.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers examined antibiotic resistance of bacteria isolated from different food samples have argued that the results of antibiotic resistance vary from study to study (Lira et al, 2004;Picozzi et al, 2005;Caro et al, 2007). It was concluded that this phenomenon may be due to high spontaneous frequency of mutation to antibiotic resistance which is not uncommon in lactobacilli (Curragh and Collins, 1992).…”
mentioning
confidence: 99%